Aplikasi Penjualan dan Pencatatan Laporan Keuangan Berbasis Web-Based Menggunakan Codeigniter pada CV. Ilusi Transpot - Robi Robiyanto; Cecep Abdul Cholik; Nani Nurheli (Jurnal Fakultas Teknik Kuningan, 2021)
A sophisticated electronic technology such as computers, where computers are one tool that can help some of the company's activities. Especially for the administration that is used as company data storage, the finance department to record company finances and the company's financial statements so that company leaders as decision makers can find out the company's development whether profit or loss. On the CV. Illusion Transpot, the data processing system is still managed manually. CV. Illusion Transpot is a private company engaged in the sale of building equipment and materials, where the equipment and building materials are purchased or even shipped from large companies. In making Sales Application and Recording of Financial Statements, it can display the availability of tools and building materials automatically, save sales transactions (sales history) in the form of receipts or memorandum of sales, transactions carried out in cash, dividing categories of goods based on price and type of equipment and building materials, and displaying goods and financial reports from sales. Sales application and report recording to store data using MySQL Database and to make the appearance of web pages using PHP and Codeigniter Framework, to run the application using a web browser application, and to support applications using Ms. Excel and PDF.